Juridical Analysis of Identity Forgery in Obstructed Marriage Cases in Sukabumi City Based on the Criminal Code (KUHP) - Kulsum A, Mutiara; Kusumah, Haidan Angga (International Journal of Law Analytics, 2024)
Crime in society, including identity and document forgery, is regulated by Articles 263-276 of the Criminal Code. This research uses the juridical-normative method to assess the application of Articles 263, 266, and Article 97 of the Civil Administration Law in cases of identity and certificate forgery involving married individuals, focusing on police report LP/B/123/III/2023/POLRES SUKABUMI/POLDA WEST JAVA. Findings show that forgery laws are often not enforced when the parties are married, despite the potential for legal action. Additionally, village officials and KUA employees involved in such cases continue in their roles despite ethical breaches, raising concerns about future violations.